2011
DOI: 10.5539/gjhs.v4n1p57
|View full text |Cite
|
Sign up to set email alerts
|

Alcoholic Beverages Drinking among Female Students in a Tourist Province, Thailand

Abstract: This study aimed to investigate alcoholic beverages drinking and predictive factors among female students. The participants were 377 subjects from 3 high schools in a tourist province, of Thailand. Data collection was done through self-administered questionnaire. Scales of the questionnaire had reliability coefficients ranging from 0.84 – 0.88. The data were analyzed by using descriptive and inferential statistics. The findings revealed as follows. About half (51%) of them have ever drunk and 10.5% of drinkers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 5 publications
4
12
0
Order By: Relevance
“…Parental behaviours are strongly influencing first alcohol use among young adolescents (White, Johnson, & Buyske, 2000). At home, young children learn how to drink alcohol from their parents (Borawski, Ievers-Landis, Lovegreen, & Trapl, 2003) because the parents believe that letting their children drink alcohol at home may enhance self-protection (Kittipichai et al, 2012). This result seems to be consistent with other research showing that adolescents are first introduced to alcohol use by parents (Eadie et al, 2010;Jones & Magee, 2014;Kittipichai et al, 2012;Ward & Snow, 2011).…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…Parental behaviours are strongly influencing first alcohol use among young adolescents (White, Johnson, & Buyske, 2000). At home, young children learn how to drink alcohol from their parents (Borawski, Ievers-Landis, Lovegreen, & Trapl, 2003) because the parents believe that letting their children drink alcohol at home may enhance self-protection (Kittipichai et al, 2012). This result seems to be consistent with other research showing that adolescents are first introduced to alcohol use by parents (Eadie et al, 2010;Jones & Magee, 2014;Kittipichai et al, 2012;Ward & Snow, 2011).…”
Section: Discussionsupporting
confidence: 79%
“…At home, young children learn how to drink alcohol from their parents (Borawski, Ievers-Landis, Lovegreen, & Trapl, 2003) because the parents believe that letting their children drink alcohol at home may enhance self-protection (Kittipichai et al, 2012). This result seems to be consistent with other research showing that adolescents are first introduced to alcohol use by parents (Eadie et al, 2010;Jones & Magee, 2014;Kittipichai et al, 2012;Ward & Snow, 2011). This result has indicated that nowadays, the parental role is different from the Thai traditional norm that parents should be good role models for their child.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study of 3005 adolescents, 12-17 years old, in Mexico found that 59% of adolescents had experienced alcohol consumption, which was signi cantly associated with increasing age, low parental supervision, and dropout rates (10). Also, a study of female students found that almost half of female high school students (12 to 17 years old) have consumed alcohol by then (11).…”
Section: Introductionmentioning
confidence: 99%